(untitled) (LEARNing Landscapes, 2010)
Ours has become,in the United States,an era when evaluation of school success:of students, teachers, and entire systems, has devolved into derivative fact—emphasizing paper-and-pencil tests.Each of these components suffers from such limited evaluation. Teachers, administrators and policy makers need to assert that a literacy program cannot be successful unless it is evaluated to highlight a wide variety of problem-setting and problem-solving processes, many of which cannot be measured exclusively on paper.